Differential expression of genes associated with non‐target site resistance in Poa annua with target site resistance to acetolactate synthase inhibitors. Issue 11 (12th July 2021) - Laforest, Martin; Soufiane, Brahim; Patterson, Eric L; Vargas, José J; Boggess, Sarah L; Houston, Logan C; Trigiano, Robert N; Brosnan, James T
Abstract: BACKGROUND: Poa annua is a pervasive grassy, self‐pollinating, weed that has evolved resistance to 10 different herbicide modes‐of‐action, third most of all weed species. We investigated constitutive overexpression of genes associated with non‐target site resistance (NTSR) in POAAN‐R3 and the response of those genes when treated with trifloxysulfuron despite the biotype having a known target site mutation in acetolactate synthase (ALS). RESULTS: Despite having an ALS target site mutation, POAAN‐R3 still had a transcriptomic response to herbicide application that differed from a susceptible biotype. We observed differential expression of genes associated with transmembrane transport and oxidation–reduction activities, with differences being most pronounced prior to herbicide treatment. CONCLUSIONS: In the P. annua biotype we studied with confirmed target site resistance to ALS inhibitors, we also observed constitutive expression of genes regulating transmembrane transport, as well as differential expression of genes associated with oxidative stress after treatment with trifloxysulfuron. This accumulation of mechanisms, in addition to the manifestation of target site resistance, could potentially increase the chance of survival when plants are challenged by different modes of action. Abstract : In Poa annua with target‐site resistance to ALS inhibitors, we observed constitutive expression of genes regulating transmembrane‐transport, and differential expression of genes associated with oxidative stress after treatment with trifloxysulfuron. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.